Characteristics of bipolar I and II disorder: A study of 8766 individuals. (22nd November 2019) - Karanti, Alina; Kardell, Mathias; Joas, Erik; Runeson, Bo; Pålsson, Erik; Landén, Mikael
Abstract: Objectives: Large‐scale studies on phenotypic differences between bipolar disorder type I (BDI) and type II (BDII) are scarce. Methods: Individuals with BDI (N = 4806) and BDII (N = 3960) were compared with respect to clinical features, illness course, comorbid conditions, suicidality, and socioeconomic factors using data from the Swedish national quality assurance register for bipolar disorders (BipoläR). Results: BDII had higher rate of depressive episodes and more frequent suicide attempts than BDI. Furthermore, the BDII group were younger at first sign of mental illness and showed higher prevalence of psychiatric comorbidity but were more likely to have completed higher education and to be self‐sustaining than the BDI group. BDII more frequently received psychotherapy, antidepressants, and lamotrigine. BDI patients had higher rate of hospitalizations and elated episodes, higher BMI, and higher rate of endocrine, nutritional, and metabolic diseases. BDI were more likely to receive mood stabilizers, antipsychotic drugs, electroconvulsive therapy, and psychoeducation. Conclusions: These results demonstrate clear differences between BDI and II and counter the notion that BDII is a milder form of BDI, but rather a more complex condition with regard to clinical course and comorbidity.